ANALISA PENGARUH INFLASI TERHADAP PERTUMBUHAN PRODUK DOMESTIK BRUTO TAHUN 2013 – 2017 - JUSUF NURDIN (EKBIS (Ekonomi & Bisnis), 2019)
Economic growth can be used as a benchmark for the success of a region’s economic development. Economic development of a region can be seen from several economic indikators such as inflation, that is increasing each year, as well as the highest GDP growth in Indonesia. This study aims to determine and analyze wow far influence Indonesia’s macroeconomic views of variable inflation and rate of unemployment and GDP. The data use from the quartely annual financial statements period 2013-2017 the macroeconomic literature from the website of Bank Indonesia, the ministery of finance and Badan Pusat Statistik Indonesia. The kind of data used is secondary data, which data is time series and cross section. The analysis technique used is panel data regression. The Research shows related between the integration of the independent variables of the macro economy with free variable.